MEMAHAMI PRAKTEK BAGI-HASIL KEB MASYARAKAT KAMPAR RIAU (Sebuah Pendekatan Etnografi) - Iwan Triyuwono, Eko Ganis Sukoharsono (JURNAL AL-IQTISHAD, 2014)
This study is aimed  to  grasp  the meaning  of a  rubber  revenue-sharingfrom the  point of view of  people  who  understand the  revenue-sharing practice  inKampar community through participatory observation. Additionally, it is aimed to deepen the understanding of  revenue-sharing practice  in  Kampar  Riau community. This study uses a qualitative method with Etnography approach. Data were collected  through  participation observation  and  open  in-depth  interviews. The data were  analyzed using Spradley model  (1997), with  includes  domainanalysis,  taxonomic  analysis, componential  analysis  and  cultural  analysis. Theresults  of this study were that gotah revenue-sharing    is    revenue-sharingcontaining the value of  KESOJUKAN  (Keadilan/Justice, Kesosialan/Socialism,Kejujuran/Honesty  and Keamanahan/Trustworthiness) in  which Gotah revenue-sharing  is a traditional custom practiced by generation and based on  Islamic values.